Correlative Relationship of Compensation, Job Stress and Style of Leadership Towards Turnover Intention - Muttaqien, Fauzan; Rizki, Via Lailatur; Fitria, Novy (STIE AMKOP, 2024)
The challenges of the financial industry in the era of society 5.0 are getting tougher. Especially for rural banks cooperatives serving the micro and small sectors. And the increasing number of Financial Services Authority Regulations (POJK) in order to adjust the climate of the financial institution industry to be conducive. The location of this research is at Eka Usaha rural banks cooperative which is one of the micro and small sector Financial Institutions that exist in Jember Regency. The purpose of this study is to analyze the correlation and influence of compensation variables, work stress and leadership style on employee turnover intention. This study is a quantitative study using a questionnaire on 50 employee respondents to obtain primary data. This study uses multiple linear regression analysis techniques. The results of the T test (partial) in the study showed that compensation had a significant effect on turnover intention, job stress did not have a significant effect on turnover intention and leadership style had a significant effect on turnover intention. The results of the determination coefficient (R2) of 0.478 or 47.8% mean that turnover intention is influenced by compensation variables, job stress and leadership style.